Here's the question you clicked on:
offthacharts
Given: x – 2(x + 2 + 2x) = 10 + 2x Prove: x = –2 Mathematical Statement Justification x – 2(x + 2 + 2x) = 10 + 2x Given x – 2(x + 2x + 2) = 10 + 2x Commutative Property of Addition x – 2(3x + 2) = 10 + 2x Combine Like Terms x – 6x – 4 = 10 + 2x Distributive Property – 5x – 4 = 10 + 2x – 7x – 4 = 10 – 7x = 14 x = –2 Division Property of Equality What are the missing justification steps, in order? Answer Distributive Property, Addition Property of Equality, Subtraction Property of Equality Combine Like Terms, Subtraction Property of Equality, Additio
Hey offthecharts, you seem to be asking a lot of the same types of questions. What are you having trouble with? I'm sure you can find someone to help you with the theory then!